Against the Pre-Archival Mentality (2006) - Koteska, Jasna (Skopje : Cultural Institution Blesok, Blesok : the art is inside, 2006)
These lines are dedicated to the book “The Female Side of the Story: The Crisis in Macedonia in 2001” by Aleksandra Bubevska and Miruse Hoxa, Evrobalkan Press, 2006.
The Female Side of the Story: The Crisis in Macedonia in 2001
Keywords: Gender Studies; War Conflict; Female Stories; Memory; Archives